El avance del COVID-19 en Santiago de Chile y su relación con las vulnerabilidades socio-ambientales urbanas - Romero, Hugo (2020)
The COVID-19 pandemic forced national governments to take social isolation actions, with the aim of stemming the progress of the virus and its brutal effects on the health and well-being of the population. This work aims to analyze the spatial behavior of this development in Santiago de Chile, the capital of the country located in the so-called Metropolitan Region, which has more than seven million inhabitants distributed in 38 communes or municipalities. By means of Landsat-7 satellite thermal images it is possible to characterize the most vegetated areas of the city, which are spatially correlated with those with lower thermal variation and the location of upper socioeconomic groups. The surface temperature values and pandemic incidence rates were crossed in each commune for the months of April, May and July 2020. The results showed that the rates of contagion arose in the richest communes of the city, located in the eastern side, such as Vitacura, Las Condes, Lo Barnechea and Providencia, in the month of April, in the beginning of the autumn. In the following month, it spreads evenly throughout the city, and in July, under the heart of the winter season, preferably locate itself in the poorest communes that reach the highest incidence rates, such as La Granja, La Pintana, San Ramón, Renca and San Joaquín, with at least 4500 contagions every 100 thousand people, which corresponds to 4.5% of its current populations. Many uncertainties persist about the spatial behavior of COVID-19 and its causes such as the natural environment, represented by the urban climate, and the socio-economic determinants of a city clearly characterized by deep socio-economic and socio-environmental inequalities.